"#discrimination": The Online Response to a Case of a Breastfeeding Mother Being Ejected from a UK Retail Premises. (February 2016) - Grant, Aimee
Background: Stigma is a significant barrier to breastfeeding. Internationally, mothers have reported stigma surrounding public breastfeeding. In the United Kingdom, the Equality Act 2010 gives women the right to breastfeed in public, including within private businesses. In April 2014, a woman who was breastfeeding in a UK sports shop was asked to leave, resulting in a localized protest by breastfeeding mothers. This resulted in the issue of public breastfeeding being highlighted in local, national, and social media. Objective: To examine online opinion regarding breastfeeding in public and protesting about the right to breastfeed in public within the context of a single case. Methods: Online user-generated content relating to the case of Wioletta Komar was downloaded from Twitter and the comments section of a UK online news source, Mail Online. Data comprised 884 comments and 1210 tweets, collected within 24 hours of the incident. Semiotic and thematic analysis was facilitated by NVivo 10. Results: Comments from Twitter were supportive (76%) or neutral (22%) regarding the protesting women and public breastfeeding. Conversely, Mail Online comments were mostly negative (85%). Mail Online posters questioned the legality of public breastfeeding, while Twitter comments acknowledged and supported women's legal right to breastfeed publicly. Many Mail Online commenters stated that they found it uncomfortable to watch breastfeeding or thought it was unnecessary to breastfeed in public. Conclusion: If the UK government is serious about increasing breastfeeding, interventions to promote public support for public breastfeeding are urgently required.